Destabilising effect of tyre burst on vehicle's dynamics. (2015) - Sassi, Sadok; Sassi, Abdelmonem
In this paper, the dynamic behaviour of a vehicle having one of its tyres burst is examined through a model-based analysis. The model considered in this study is a classical one, considering only straight line motion in Z-direction. In total, nine degrees of freedom are analysed: four translations of the un-sprung masses, one translation of the centre of gravity, two rotations of the body and two translations of the seat and its support. When a tyre blows out (for example in the front-left side), several changes are observed to occur. These changes affect the vehicle stability and geometry, the operating conditions and the tyre-road interaction. The numerical simulation of the effects of tyre deflations on vehicle behaviour was achieved by using MATLAB/Simulink. It is concluded that the blast coming from the tyre blowout generates enough energy to excite the wheel structure resonances but has relatively little effect on the comfort of the driver. The main effect is observed to be on the safety of the vehicle which, under the action of a lateral push, is deviated from its trajectory towards the side of the deflated tyre.